A history of U.S. communications intelligence during World War II : policy and administration - Benson, Robert Louis (United States cryptologic history. World War II, 1997)
"A study of high-level policy, administration, and organization of COMINT during WWII and how it was controlled and directed by each military service and how these services related to each other and to their British counterparts"--Resource description page.